2014
DOI: 10.1002/2014gl061869
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the loss cone for energetic particles

Abstract: The optimal pitch angle which maximizes the penetration distance, along the magnetic field, of relativistic charged particles injected from the midplane of an axisymmetric field is investigated analytically and numerically. Higher-order terms of the magnetic moment invariant are necessary to correctly determine the mirror point of trapped energetic particles, and therefore the loss cone. The modified loss cone resulting from the inclusion of higher-order terms is no longer entirely defined by the pitch angle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…The denominator, L B , of the small parameter is the characteristic gradient length scale of the mangetic field L −1 B = |∇ lnB|. For relativistic electrons Porazik et al (2014) showed that higherorder terms of the magnetic moment invariant are necessary to correctly determine the mirror point of trapped energetic particles, and therefore the loss cone. Figure 6 (left) shows the pitch angles (δ) that would lead to precipitation for different azimuthal injection angles (λ) as a function of electron energy at 10 R e .…”
Section: Beam Injection Into the Loss Conementioning
confidence: 99%
See 1 more Smart Citation
“…The denominator, L B , of the small parameter is the characteristic gradient length scale of the mangetic field L −1 B = |∇ lnB|. For relativistic electrons Porazik et al (2014) showed that higherorder terms of the magnetic moment invariant are necessary to correctly determine the mirror point of trapped energetic particles, and therefore the loss cone. Figure 6 (left) shows the pitch angles (δ) that would lead to precipitation for different azimuthal injection angles (λ) as a function of electron energy at 10 R e .…”
Section: Beam Injection Into the Loss Conementioning
confidence: 99%
“…Edges of loss cones for (Middle) an electron initialized from 10 Re at the equatorial plane of a dipole field for different energies and (Right) for a 7-MeV electron initialized from different distances at the equatorial plane of a dipole field. The black dashed line corresponds to the unmodified loss cone for injection from the equatorial plane (Adapted from Porazik et al, 2014). FIGURE 7 | Solution to the envelope equations without beam perveance (blue lines).…”
Section: Beam Propagationmentioning
confidence: 99%
“…In this case, λ and β are azimuthal and lateral angles for a spherical coordinate system with the z-axis aligned with v 0 . As described by Porazik et al (2014), v 0 is not exactly aligned with the magnetic field and will always have a perpendicular component that is aligned with the drift. The transformation T is therefore simply a rotation of the system about the normal axisN by an angle α 0 such that cos(α 0 ) = v 0 · B/vB.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…It is also suggested by simple linear analysis that relativistic beams traveling through the magnetosphere are stable to two-stream instabilities (Galvez and Borovsky, 1988), and relativistic beams entering the ionosphere are stable to resistive hose, ion hose, and filamentation instabilities (Gilchrist et al, 2001). Nevertheless, relativistic beams do come with their own issues, as discussed by Porazik et al (2014), due to the fact that the first adiabatic invariant will not necessarily be conserved to zeroth order. Using a second order asymptotic expansion derived by Gardner (1966), it was shown that the dependence on field-line curvature in the higher order terms of µ has a substantial effect on the loss cone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation